1999
DOI: 10.1002/(sici)1097-0185(19990901)256:1<7::aid-ar2>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal hypothyroidism and radioactive iodine on rat embryonal development: Thyroid C‐cells

Abstract: There have been no works devoted to the study of the influence of 131 I and maternal 131 I-induced hypothyroidism on the state of the C-cells in the thyroid gland of the developing embryos. A study was made on the effect of a dose of 150 µCi 131 I (0.5 Gy) leading to hypothyroidism in rats, on 35 mother rats and 168 newborn pups. The mother rats were divided into control and four treated groups which were injected with 131 I before pregnancy, on gestation days 5, 10, and 16, respectively. Immunohistochemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…We have reviewed the literature, both in humans and experimental animals, describing C-cell behaviour in different pathological states of the thyroid gland, but the data are conflicting. In some cases of induced hypothyroidism in rats, a C-cell hyperplasia is described (Peng et al 1975;Stoll et al 1978;Usenko et al 1999), but opposing results are also reported (Bugnon et al 1978;Logonder-Mlinsek et al 1985;Zbucki et al 2007). Similarly, in human pathology, C-cell hyperplastic changes, as well as opposing findings, have been reported in both hypothyroid and hyperthyroid states (Dhillon et al 1982;Scheuba et al 2000;Dadan et al 2001).…”
Section: Introductionmentioning
confidence: 96%
“…We have reviewed the literature, both in humans and experimental animals, describing C-cell behaviour in different pathological states of the thyroid gland, but the data are conflicting. In some cases of induced hypothyroidism in rats, a C-cell hyperplasia is described (Peng et al 1975;Stoll et al 1978;Usenko et al 1999), but opposing results are also reported (Bugnon et al 1978;Logonder-Mlinsek et al 1985;Zbucki et al 2007). Similarly, in human pathology, C-cell hyperplastic changes, as well as opposing findings, have been reported in both hypothyroid and hyperthyroid states (Dhillon et al 1982;Scheuba et al 2000;Dadan et al 2001).…”
Section: Introductionmentioning
confidence: 96%
“…С помощью этой модели были воспроизведены такие изменения, которые соответствовали врожденному гипотиреозу у человека, то есть атрофия клеток и снижение массы головного мозга, а также изменения массы тела в потомстве животных [18]. Другие находки включают важные изменения в щитовидной железе у крыс, а именно повреждения клеток щитовидной железы, уменьшение толщины стенок кровеносных сосудов, сильные воспалительные реакции и некротизирование фолликулярных клеток железы [19], а также гиперплазии и гипотрофии клеток, положительных к кальцитонину [19][20]. Достоинством модели является использование небольшого количества радиоактивного йода для развития дисфункции и деструкции щитовидной железы, приводящей к гипотиреозу.…”
Section: таблица 1 классификация экспериментальных моделей гипотиреозаunclassified
“…Hypothyroidism, for example, is characterized by decreased numbers of parafollicular cells, 48 but hypothyroidism in expectant mothers has been found to cause an increase in the size of parafollicular cells in newborns. 49 Harmful environmental effects due to microgravity or hypergravity in outer space are known to provoke a decrease in the number of parafollicular cells, 50 while low frequency EMFs increase their numbers. 45 In the present experiment, exposure of rat thyroid gland to RF at 2.45 GHz and 0.102 AE 12.10 -3 SAR increased HSP-90 marking in the parafollicular cells.…”
Section: The Observed Localization Of the Expression Of Thismentioning
confidence: 99%